(untitled) (Global Journal of Human-Social Science, 2017)
The aim of this paper is to examine the Affordable Housing Policy in Jos Nigeria A diminishing dream after 35 years with a view to make recommendations towards addressing the housing problems by examining the national Housing Policy National Housing Fund and the National and housing development The purposive random sampling has been employed to select the local government areas that have the Low-cost housing in Jos Metropolis Utilising secondary data based on the 2006 National population census data National Housing Policy NHP National Housing Fund NHF and the Land Use Act of 1978 the study analysed the quantity of housing delivered by each Local Government Thematic and content analysis were used to analyse the data The non-implementation of the National Housing policies from the Federal State and Local government level due to the high level corruption institutional Deficiency land issues illegal land and changes in the Land Use in most layouts making it very difficult to achieved the aim of the National Housing Policy at the three tiers of Government as if the policy was not well articulated Based on these findings recommendations were made for policy makers academia and for practitioners